Multiomics unravels the complexity of male obesity: a prospective observational study - Papadakis, Georgios E.; Favre, Lucie; Zouaghi, Yassine; Vionnet, Nathalie; Niederländer, Nicolas J.; Adamo, Michela; Acierno, James S.; Berdous, Dassine; Boizot, Alexia; Meylan, Jenny; Ivanisevic, Julijana; Paccou, Emmanuelle; et al. (Journal of translational medicine, 2025)
Background Obesity is associated with varying degrees of metabolic dysfunction. In this study, we aimed to discover markers of the severity of metabolic impairment in men with obesity via a multiomics approach. Methods Thirty-two morbidly men with obesity who were candidates for Roux-en-Y gastric bypass (RYGB) surgery were prospectively followed. Nine healthy adults served as controls. Deep phenotyping, including targeted metabolomics, transcriptomics, and brain magnetic resonance imaging (MRI), was performed. Results Testosterone emerged as a key contributor to phenotypic variability via principal component analysis and was therefore used to further categorize obese patients as having or not having hypogonadotropic hypogonadism (HH). Despite having comparable body mass indices, obese individuals with HH presented with worse metabolic defects than obese individuals without HH, including higher insulin resistance, as well as MRI signs of hypothalamic inflammation and a specific blood transcriptomics signature. The upregulated genes were involved mainly in inflammation, mitochondrial function, and protein translation. Integration of gene expression and clinical data revealed high FGF21 and low cortisol levels as the top markers correlated with the transcriptomic signature of metabolic risk. Following RYGB-induced substantial weight loss, testosterone levels markedly increased in both obese individuals with and without HH, challenging the current definition of hypogonadism. A longitudinal study in a subset of men with obesity following bariatric surgery revealed a unique FGF21 trajectory with a sharp peak at one month post-RYGB that correlated with metabolic and reproductive improvements. Conclusions Combining clinical, biochemical, and molecular markers allows adequate stratification of metabolic risk in men with obesity and provides novel tools for personalized care.